Kajian Simulasi Fem 3D : Keausan Pahat Twist Drill pada Pemesinan Bor Mikro Material Ti-6Al-4V - Gusri Akhyar Ibrahim; Yanuar Burhanuddin; Aufadhia (Politeknik Manufaktur Negeri Bangka Belitung, 2020)
Titanium is a material that has a good strength to weight ratio, excellent corrosion resistance, and resistant to high or low temperatures Titanium alloys that are used in various industrial fields, one of them is the Ti6Al4V alloy. Micro drilling has a high rotational speed which results in tool wear, high temperatures, and surface roughness. This research uses The Finite Element Method (FEM) simulation. The application used is DEFORM 3D based on parameters from previous studies. The purpose of this research is to identify the progress of tool wear in a simulated manner on the Ti6Al4V alloy micro-dilling and analyze the tool wear on the Ti6Al4V alloy micro-drilling under dry machining conditions. Machining trials used CNC micro-drilling at various of cutting parameters such as cutting speed of 10.000 and 15.000 rpm. The results showed that the tool wear progress at the 5th hole was 0.00346 mm, the tool wear progress at the 10th hole was 0.00462 mm and the tool wear progress at the 15th hole was 0.00525 mm. Analyzing tool wear in simulated machining and experimental machining in dry conditions has a high wear value. Tool wear is simulated by measuring the radius of the tool in the 15th hole valued at 0.09973 mm. Tool wear is experimentally measured from the tool radius in the 15th hole valued at 0.0101 mm. The tool mesh is changed due to the tool wear. The tool mesh in the 5th hole is worth 17372 mesh. The tool mesh in the 10th hole is 15662 mesh. The tool mesh in the 15th hole was highly reduced by 13021 mesh. Tool wear affects the change in tool mesh. With increasing tool wear then tool mesh is reduced. The next cause of tool wear is the tool temperature in the machining process.